Analisis Implementasi Kebijakan Rujuk Balik Diabetes Melitus di Puskesmas X Kota Tangerang Selatan - Hamzah, Aries; Sulistiadi, Wahyu (UI Scholars Hub, 2017)
The Increasing of Prevalence of Diabetes Mellitus will increase health expenditure in Universal Health Coverage (JKN). The role of health primary care as the front side in health services on back referral for Diabetes disease becomes very important. The purpose of this study was to determine the effectiveness of policy implementation in Diabetes Mellitus back referral behind PHC X 2014. This study used a qualitative approach to the study design content analysis and triangulation methods. Primary data obtained by in-depth interviews, focus groups, and observations in the field. Secondary data were obtained from policy documents and literature. The results showed ineffectiveness of policy implementation in Diabetes Mellitus back referral in X Primary Health Care. This study recommends to revise and make the existing regulations comprehensive in order to the implementation can be effective and further, there is no gap in Diabetes back referral policy implementation